Tax Expenditures: An Analysis of Conventional Literature - Bawa, Kamal (Auckland University of Technology, 2023)
Purpose: The study aims to examine the conventional literature on tax expenditures. This study focuses on the tax subsidies and tax concessions provided to charitable organizations and other non-profit organizations (NPOs) to achieve the non-revenue objective of the tax expenditures. Theoretical Framework: This study explains the key concepts of tax expenditures including its categorization and significance. Methodology: A systematic literature review method was used to synthesize the tax expenditures scholarship. This study involves the secondary data collection of published research papers. The data was analyzed manually by preparing annotated bibliographies to extract the key information. Findings: The results of this study show that tax subsidies have a significant impact on tax expenditure objectives. However, there are some countries in which tax subsidies are incompetent to achieve their specified goals. In addition, this study also gives recommendations that tax concessions can fulfill the public benefit objective when NPOs and charities are beneficial to a broad or wider community. NPOs and charities should get the same tax treatment as for-profit organizations or minor tax treatment if they are involved in business or commercial activities. Lastly, there is no need for a statutory definition of a charity to achieve public benefit purposes. Implications: The effective achievement of tax expenditure goals through tax subsidies gives easiness to the organizations to produce certain goods. NPOs and charities can provide services in more efficient way by fulfilling the public objective. Originality/Value: This study contributes to the taxation literature and discipline by examining the effectiveness of tax subsidies and tax concessions covered in different policies at the global level.
Keywords: Tax Expenditures; Tax Subsidies; Non-tax Objective; Tax Concessions; Public Benefit